mu(+)-SR studies of the weak ferromagnets CoCO3 and NiCO3 - Lancaster, T; Blundell, S; Pratt, F; Kurmoo, M (2003)
We present the results of zero-held mu(+)-SR measurements on CoCO3 and NiCO3. Both compounds are rhombohedral antiferromagnets which exhibit a spontaneous weak magnetisation below 22.2 and 17.2 K, respectively. This arises due to an anisotropic superexchange (Dzyaloshinsky-Moriya) interaction. We have studied the temperature dependence of the internal field in the ordered state and the magnetic fluctuations in the paramagnetic state. We describe the possible muon-site obtained from dipolar-field calculations. (C) 2002 Elsevier Science B.V. All rights reserved.